Titanium carbide-based catalytic material capable of degrading sulfur hexafluoride in air atmosphere as well as preparation method and application of titanium carbide-based catalytic material
By using titanium carbide-based catalytic material as a combination of active site center and silicon carbide support, the problem of efficient degradation of sulfur hexafluoride under air atmosphere is solved, and an efficient and economical degradation effect is achieved, which is suitable for industrial production.
Patent Information
- Application Number
- CN202411791165.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-11
AI Technical Summary
The prior art is difficult to efficiently degrade sulfur hexafluoride (SF6) under air atmosphere, especially at lower temperatures, which lack effective degradation mechanisms and techniques.
Titanium carbide (TiC) is used as the center of the active site and silicon carbide is used as the support to prepare TiC-based catalytic material through physical mixing and grinding, which can efficiently degrade sulfur hexafluoride under an air atmosphere.
It has achieved efficient degradation of sulfur hexafluoride in an air atmosphere at 500-600℃, with a degradation rate of up to 99.33%, and the degradation amount of SF6 on unit mass TiC reaches 385.0mL g-1. It has a simple process and low cost, which is suitable for large-scale production.
Smart Images

Figure CN119588391A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of material technology, and in particular to a titanium carbide-based catalytic material capable of degrading sulfur hexafluoride in an air atmosphere, and a preparation method and application thereof. Background Art
[0002] Greenhouse gases are the main culprit for global warming. In recent years, climate change has posed a threat to the sustainable development of human society. Sulfur hexafluoride (SF6) is a greenhouse gas that should be restricted in the Kyoto Protocol. Its global warming potential (GWP) is very high, 24,300 times that of carbon dioxide (CO2). The insulation strength of sulfur hexafluoride gas is more than 2.5 times that of air, and its arc extinguishing ability as an arc extinguishing medium is more than 100 times that of air. Due to its superior electrical properties, sulfur hexafluoride has been widely used as a protective gas in ultra-high voltage power transmission and transformation equipment and electrical switches. At present, the annual SF6 gas discharged into the atmosphere is equivalent to 125 million tons of CO2 gas. With the development of the power system, it is expected that the emission of SF6 will continue to increase in the future, which is bound to greatly increase the pressure on environmental protection. Therefore, it is urgent to control the emission of sulfur hexafluoride and find a method to degrade sulfur hexafluoride.
[0003] Titanium carbide (TiC) materials have the characteristics of clear layered structure, good electrical conductivity, high thermal stability, good metallic conductivity, large surface area, and small energy band gap. Therefore, people are increasingly interested in the application of TiC materials in the field of thermal catalysis.
[0004] At present, there are many methods for degrading sulfur hexafluoride, such as adsorption, traditional industrial thermal decomposition, photodegradation, plasma method and catalytic degradation. Among them, the catalytic degradation method has received special attention. There are mainly three types of catalysts for the catalytic degradation of sulfur hexafluoride: metal oxides, metal phosphates, and supported metal catalysts. These catalysts are all carried out in an argon or nitrogen atmosphere above 600°C, and there is currently a lack of degradation mechanism and technical research under low temperature atmospheric environment conditions. For example, Zhang Jia et al. (CN103007736A) used electroplating sludge to degrade sulfur hexafluoride more effectively, but its degradation process needs to be carried out under the protective atmosphere of nitrogen. Under realistic conditions, sulfur hexafluoride is in the atmosphere, and the protective atmosphere of nitrogen greatly hinders the practical application of SF6 degradation catalysts. Therefore, it is necessary to develop a simple, environmentally friendly catalytic material that can degrade SF6 in a general air atmosphere.
[0005] The Chinese patent application document with publication number CN113244939A discloses a silicon carbide-iron oxide composite material for decomposing sulfur hexafluoride in an atmospheric environment. The composite material is a powder composite material with a heat conductive material as a carrier and iron oxide as the active site center, and the mass ratio of the carrier to the iron oxide is 10:1 to 60:1. It can realize the activation and decomposition of sulfur hexafluoride and decompose sulfur hexafluoride in an atmospheric environment, which conforms to the actual situation and has great practical potential. The catalytic material is prepared by a simple self-assembly chemical deposition method, which has a simple process, low processing cost, and is suitable for large-scale production. However, the above method requires a high temperature of 600°C to degrade SF6, and the preparation process of the catalytic material is cumbersome, not suitable for industrial production, and the degradation energy consumption is also high.
[0006] A Chinese patent application document with publication number CN116078416A discloses a manganese-based catalytic material for degrading sulfur hexafluoride in an air atmosphere. The manganese-based catalytic material uses metallic manganese as the active site center and uses one or more of silicon carbide, silicon dioxide, rectorite, mullite, and hydrotalcite as a carrier. The manganese-based catalytic material can be used to catalytically degrade sulfur hexafluoride in an air atmosphere. The manganese-based catalytic material prepared by the manganese-based catalytic material can degrade sulfur hexafluoride in an air atmosphere, which is different from the previous technology that requires degradation in a protective atmosphere of nitrogen or argon. It is very in line with the actual situation and has great practical potential. It can be prepared by a simple physical grinding method without sintering, with a simple process and low processing cost, and is suitable for large-scale production. However, when the temperature is 500°C, the maximum degradation rate of SF6 by the above-mentioned catalytic material is only 85%, and efficient degradation of SF6 cannot be achieved.
[0007] The Chinese patent application document with publication number CN116474762A discloses a catalytic material based on molybdenum dioxide for degrading sulfur hexafluoride in an air atmosphere. The catalytic material uses molybdenum dioxide as the active site center and one or more of silicon carbide and silicon dioxide as a carrier. The molybdenum dioxide material is used to catalyze the degradation of sulfur hexafluoride in an air atmosphere. The MoO2-based catalytic material uses MoO2 as the active site center and one or more of silicon carbide and silicon dioxide as a carrier. It can be prepared by a simple physical grinding method without sintering, with a simple process and low processing cost, and is suitable for large-scale production. However, when the temperature is 500°C, the maximum degradation rate of the above-mentioned catalytic material for SF6 is only 73.33%, and the unit degradation amount is only 123.42mL g -1 , it is impossible to achieve efficient degradation of SF6. Summary of the invention
[0008] The technical problem to be solved by the present invention is how to efficiently degrade SF6 in an air atmosphere.
[0009] The present invention solves the above technical problems through the following technical means:
[0010] A titanium carbide-based catalytic material capable of degrading sulfur hexafluoride in an air atmosphere, wherein titanium carbide is used as an active site center and silicon carbide is used as a carrier, wherein the active site center is dispersed on the carrier; the mass of the titanium carbide accounts for 10-20% of the mass of the catalytic material.
[0011] Preferably, the mass of the titanium carbide accounts for 20% of the mass of the catalytic material.
[0012] The present invention also proposes a method for preparing the titanium carbide-based catalytic material capable of degrading sulfur hexafluoride in an air atmosphere, comprising the following steps: physically mixing titanium carbide and silicon carbide to obtain the titanium carbide-based catalytic material capable of degrading sulfur hexafluoride in an air atmosphere.
[0013] Preferably, the method for preparing the titanium carbide-based catalytic material capable of degrading sulfur hexafluoride in an air atmosphere comprises the following steps: mixing titanium carbide and silicon carbide and then grinding them to obtain the titanium carbide-based catalytic material capable of degrading sulfur hexafluoride in an air atmosphere.
[0014] The present invention also proposes an application of the titanium carbide-based catalytic material capable of degrading sulfur hexafluoride in an air atmosphere in degrading sulfur hexafluoride.
[0015] The present invention also proposes a method for degrading sulfur hexafluoride using the titanium carbide-based catalytic material capable of degrading sulfur hexafluoride in an air atmosphere, comprising the following steps: placing the titanium carbide-based catalytic material capable of degrading sulfur hexafluoride in an air atmosphere in a reaction device, introducing a mixed gas of sulfur hexafluoride and air, and degrading sulfur hexafluoride at 500-600°C.
[0016] Preferably, in the mixed gas of sulfur hexafluoride and air, the volume concentration of sulfur hexafluoride is 3 vol.% to 60 vol.%.
[0017] Preferably, the degradation of sulfur hexafluoride is carried out at 500°C.
[0018] Preferably, the flow rate of the mixed gas of sulfur hexafluoride and air is 10 ml / min.
[0019] Preferably, the time for degrading sulfur hexafluoride is 10-40 minutes. (The degradation rate is highest during this time)
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] (1) The TiC-based catalytic material of the present invention uses TiC as the active site center and silicon carbide as the carrier. It can be prepared by a simple physical grinding method without sintering, has a simple process, low processing cost, and is suitable for large-scale production.
[0022] (2) The catalytic material of the present invention has excellent degradation ability for sulfur hexafluoride and basically does not produce toxic gases, which is in line with the concept of environmental protection.
[0023] (3) The catalytic material of the present invention can degrade sulfur hexafluoride in an air atmosphere, which is different from the previous technology that requires degradation in a protective atmosphere of nitrogen or argon. It is very consistent with the actual situation and has great practical potential.
[0024] (4) The catalytic material of the present invention has a very rapid response to the degradation of sulfur hexafluoride and a long service life. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a transmission electron microscope image of the TiC-based catalytic material prepared in Example 1 of the present invention;
[0026] Figure 2 A transmission electron microscope energy dispersive X-ray spectroscopy image of the TiC-based catalytic material prepared in Example 1 of the present invention;
[0027] Figure 3 This is a schematic diagram of a device for catalytic degradation of sulfur hexafluoride according to the present invention;
[0028] Figure 4 The curve showing the change of sulfur hexafluoride degradation efficiency with increasing reaction time in Example 2 of the present invention;
[0029] Figure 5 The effect curve of different compositions of the TiC-based catalytic material of the present invention on the degradation efficiency of sulfur hexafluoride and the comparison of the degradation amount;
[0030] Figure 6 This is a curve showing the effect of different carriers of the TiC-based catalytic material of the present invention on the degradation efficiency of sulfur hexafluoride;
[0031] Figure 7 This is the influence curve of different treatment temperatures on the degradation efficiency of sulfur hexafluoride in the present invention;
[0032] Figure 8 This is a curve showing the influence of different active centers on the degradation efficiency of sulfur hexafluoride in the present invention. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] Unless otherwise specified, the test materials and reagents used in the following examples can be obtained from commercial sources.
[0035] If no specific techniques or conditions are specified in the examples, they can be carried out according to the techniques or conditions described in the literature in the art or according to the product instructions.
[0036] Example 1
[0037] 1. Preparation of TiC-based Catalytic Materials
[0038] TiC was used as the active center and silicon carbide was used as the carrier. The mass ratio of TiC in the catalytic material was controlled to be 20wt%. 0.2g of TiC and 0.8g of silicon carbide were mixed and manually ground for three minutes to obtain a powdered TiC-based catalytic material.
[0039] Transmission electron microscope images of the prepared TiC-based catalyst materials are shown in Figure 2. Figure 1 Then, the TiC-based catalytic material was characterized by transmission electron microscopy energy dispersive X-ray spectroscopy, as shown in Figure 2 As shown by Figure 2 It can be seen that TiC is dispersed in the silicon carbide carrier to form a TiC / SiC structure.
[0040] 2. Device for treating sulfur hexafluoride using TiC-based catalytic materials
[0041] like Figure 3 The figure shows a schematic diagram of the structure of a device for treating sulfur hexafluoride with TiC-based catalytic materials, which includes the following components: 1 pure sulfur hexafluoride gas cylinder; 2 gas flow meter; 3 gas mixer; 4 quartz reaction tube; 5 tubular furnace; 6 alkali solution recovery device; 7 gas chromatograph; A air inlet; B reacted gas outlet. Among them: the air entering from the air inlet A and the sulfur hexafluoride gas in the pure sulfur hexafluoride gas cylinder 1 pass through the gas flow meter 2, enter the gas mixer 3 to be mixed, and then are sent to the quartz reaction tube 4, the quartz reaction tube 4 has a TiC-based catalytic material built in, the quartz reaction tube 4 is set in the tubular furnace 5, and is heated to the treatment temperature by the tubular furnace 5. The gas treated from the quartz reaction tube 4 is sent to the alkali solution recovery device 6, and is discharged from the reacted gas outlet B after being detected by the gas chromatograph 7.
[0042] 3. A process for treating sulfur hexafluoride with a TiC-based catalytic material, comprising the following steps:
[0043] (1) Configuration of sulfur hexafluoride waste gas:
[0044] The sulfur hexafluoride waste gas used in the experiment is a mixture of sulfur hexafluoride and air in a simulated configuration. In this embodiment, the concentration of sulfur hexafluoride is controlled at 10 vol.% by the gas flow meter 2 and the gas mixer 3, and the flow rate is 10 ml / min.
[0045] (2) The mixed and ground TiC-based catalytic material is filled into the quartz reaction tube 4, and the mixed gas of sulfur hexafluoride and air is continuously fed into the quartz reaction tube 4 to wait for treatment.
[0046] (3) The quartz reaction tube 4 is placed in a tubular furnace 5, and the temperature is controlled at 500° C. The tail gas from the quartz reaction tube 4 is passed into an alkali solution recovery device 6. The tail gas is absorbed by a 5 mol / L sodium hydroxide solution and then detected by a gas chromatograph 7 and can be directly discharged into the atmosphere.
[0047] Example 2
[0048] The TiC-based catalytic material preparation method, treatment device and treatment process of Example 1 are used, except that the treatment time after the quartz reaction tube is heated to 500°C is adjusted, and its effect on the degradation efficiency is tested. The results are as follows: Figure 4 shown.
[0049] from Figure 4 It can be seen that when the temperature just rises to 500 °C, sulfur hexafluoride has a good degradation efficiency. In the degradation range of 10-40 min, the degradation rate is above 85%, and the highest degradation rate is 99.33% (corresponding to the degradation time of 20-30 min). The sustainable degradation is 110 min. The SF6 degradation amount per unit mass on TiC in the total degradation time is 385.0 mL g -1 .
[0050] Example 3
[0051] The TiC-based catalytic material preparation method, treatment device and treatment process of Example 1 are used, except that the ratio of silicon carbide and TiC in the TiC-based catalytic material is adjusted (the mass of the prepared TiC-based catalytic material is 1 g), as shown in Table 1, and its effect on the degradation efficiency is tested. The results are as follows: Figure 5 shown.
[0052] Table 1. Effects of composition and ratio of different TiC-based catalytic materials on degradation
[0053]
[0054] analyze:
[0055] The mass ratio of TiC in the catalytic material has a great influence on the SF6 degradation effect. The highest degradation rate of the TiC-based catalytic material with 2.5wt% TiC is 5.72%, and the SF6 degradation amount per unit mass of TiC is 11.5mL g -1 The highest degradation rate of TiC-based catalytic material with 10wt% TiC was 68.56% (corresponding to a degradation time of 20min), and the SF6 degradation amount per unit mass of TiC reached 297.0mL g -1 , the degradation life is 100 minutes. When the specific gravity of TiC rises to 20wt%, the maximum degradation rate rises to 99.33% (corresponding to a degradation time of 20-30min), and the SF6 degradation amount per unit mass of TiC in the total degradation time is 385.0mL g -1 However, when the TiC content increases further, the degradation effect of SF6 begins to decline. When the TiC content reaches 30wt%, the SF6 degradation per unit mass of TiC is almost reduced to a quarter, from 385.0mL g -1 Down to 90.8 mL g -1 . This is because SiC plays the role of electron donor and dispersant in the composite material. On the one hand, the reduction of SiC limits the electron diffusion efficiency and greatly weakens the Ti-C degradation site; at the same time, the metal oxide fluoride will re-sinter at high temperature, which may cause the contact area to decrease, block the gas flow, and reduce the reaction rate. Therefore, the TiC content in the TiC-based catalyst material is preferably 20wt%.
[0056] Example 4
[0057] The TiC-based catalytic material preparation method, treatment device and treatment process of Example 1 are used, except that the choice of carrier is adjusted as shown in Table 2, and its effect on the degradation efficiency is tested. The results are as follows: Figure 6 shown.
[0058] Table 2. Effects of different carrier selections on degradation
[0059]
[0060] analyze:
[0061] Choosing different carriers will have a huge impact on the performance of TiC-based catalytic materials. When SiO2 is selected as the carrier, SF6 cannot be degraded at 500°C. This is because the crystal size of SiO2 is large and the specific surface area is small, which is not conducive to the adsorption of SF6. At the same time, the charge distribution inside the TiC material is very uniform, which is not conducive to the transfer of electrons to SF6 molecules, thus failing to achieve the degradation effect. When TiO2 powder is selected as the carrier, there is still no degradation effect on SF6. When no carrier is selected and only active ingredients are used for degradation, the maximum degradation rate can reach 98.53%, but the unit degradation amount is only 98.31 mL g -1 . The best degradation effect of SF6 can be achieved when SiC is used as a carrier. SiC has high hardness and is a commonly used abrasive. After mixing with TiC, the size of the material is more uniform, which is conducive to adsorption and reaction. In addition, SiC has the properties of a semiconductor, which can redistribute electrons between TiC and SiC, and the electronic effect can be used to accelerate the activation and degradation of SF6. Therefore, the most preferred carrier for TiC-based catalytic materials is silicon carbide.
[0062] Example 5
[0063] The TiC-based catalytic material preparation method, treatment device and treatment process of Example 1 are used, except that the treatment temperature of the tube furnace is adjusted as shown in Table 3, and the effect of the treatment temperature on the degradation efficiency is tested. The results are as follows: Figure 7 shown.
[0064] Table 3. Effect of different degradation temperatures on degradation
[0065]
[0066] analyze:
[0067] The degradation temperature affects the degradation effect of TiC-based catalytic materials. At 400°C, TiC-based catalytic materials cannot activate SF6. When the temperature rises to 500°C, TiC-based catalytic materials begin to react with SF6. At this time, the highest degradation rate is 99.33%, and the SF6 degradation amount per unit TiC reaches 385.0 mL g -1 When the temperature is further increased to 600 °C, SF6 can achieve 100% degradation (within the degradation range of 10-200 min), and the unit degradation amount reaches 1062.6 mL g -1 , the degradation life is as long as 300 minutes. Therefore, it is not difficult to see that temperature has a great influence on the degradation effect of SF6, and high temperature is conducive to the activation and degradation of SF6 molecules by TiC-based catalytic materials. Considering energy saving and economy, the degradation temperature is preferably 500℃.
[0068] Example 6
[0069] The TiC-based catalytic material preparation method, treatment device and treatment process of Example 1 are used, except that the selection of active centers is adjusted, as shown in Table 4, and the influence of active centers on degradation efficiency is tested. The results are as follows: Figure 8 shown.
[0070] Table 4. Effects of different active centers on degradation
[0071]
[0072] analyze:
[0073] The active center will affect the degradation effect of SiC carrier catalytic materials. When the active center is TiO2 and Ti(SO4)2, the SF6 degradation amount per unit mass of the active center is 0, indicating that TiO2 and Ti(SO4)2 have no catalytic degradation effect on SF6 after being composited with SiC. Therefore, it is not difficult to see that the composition of the active center has a great influence on the degradation effect of SF6, and the composite catalytic material composed of TiC and SiC has the best activation and degradation effect on SF6 molecules.
[0074] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A titanium carbide-based catalytic material capable of degrading sulfur hexafluoride in an air atmosphere, characterized in that: It uses titanium carbide as the active site center and silicon carbide as the carrier, and the active site center is dispersed on the carrier; the mass of the titanium carbide accounts for 10-20% of the mass of the catalytic material.
2. The titanium carbide-based catalytic material capable of degrading sulfur hexafluoride in an air atmosphere according to claim 1, characterized in that: The mass of the titanium carbide accounts for 20% of the mass of the catalytic material.
3. A method for preparing a titanium carbide-based catalytic material capable of degrading sulfur hexafluoride in an air atmosphere as claimed in claim 1 or 2, characterized in that: The following steps are involved: The titanium carbide-based catalytic material capable of degrading sulfur hexafluoride in an air atmosphere is obtained by physically mixing titanium carbide and silicon carbide.
4. The method for preparing a titanium carbide-based catalytic material capable of degrading sulfur hexafluoride in an air atmosphere according to claim 3, characterized in that: The following steps are involved: Titanium carbide and silicon carbide are mixed and then ground to obtain the titanium carbide-based catalytic material capable of degrading sulfur hexafluoride in an air atmosphere.
5. Use of the titanium carbide-based catalytic material capable of degrading sulfur hexafluoride in an air atmosphere as claimed in claim 1 or 2 in degrading sulfur hexafluoride.
6. A method for degrading sulfur hexafluoride using the titanium carbide-based catalytic material capable of degrading sulfur hexafluoride in an air atmosphere as claimed in claim 1 or 2, characterized in that: The following steps are involved: A titanium carbide-based catalytic material capable of degrading sulfur hexafluoride in an air atmosphere is placed in a reaction device, and a mixed gas of sulfur hexafluoride and air is introduced to degrade sulfur hexafluoride at 500-600°C.
7. The method for degrading sulfur hexafluoride using the titanium carbide-based catalytic material capable of degrading sulfur hexafluoride in an air atmosphere according to claim 6, characterized in that: In the mixed gas of sulfur hexafluoride and air, the volume concentration of sulfur hexafluoride is 3 vol.% to 60 vol.%.
8. The method for degrading sulfur hexafluoride using the titanium carbide-based catalytic material capable of degrading sulfur hexafluoride in an air atmosphere according to claim 6, characterized in that: The degradation of sulfur hexafluoride was carried out at 500°C.
9. The method for degrading sulfur hexafluoride using the titanium carbide-based catalytic material capable of degrading sulfur hexafluoride in an air atmosphere according to claim 6, characterized in that: The flow rate of the mixed gas of sulfur hexafluoride and air is 10 ml / min.
10. The method for degrading sulfur hexafluoride using the titanium carbide-based catalytic material capable of degrading sulfur hexafluoride in an air atmosphere according to any one of claims 6 to 9, characterized in that: The time for degrading sulfur hexafluoride is 10-40 minutes.
Citation Information
Patent Citations
Method for high efficiency treatment of?sulfur hexafluoride (SF6) pollution gas?through electroplating sludge
CN103007736A
Silicon carbide-iron oxide composite material for decomposing sulfur hexafluoride in atmospheric environment and application thereof
CN113244939A
Catalytic material based on elemental manganese for degrading sulfur hexafluoride in air atmosphere
CN116078416A
Molybdenum dioxide-based catalytic material for degrading sulfur hexafluoride in air atmosphere
CN116474762A
Cited By
Preparation method and application of vanadium-doped titanium dioxide composite material
CN120771857A